Synthesis, First-Principle Simulation, and Application of Three-Dimensional Ceria Nanoparticles/Graphene Nanocomposite for Non-Enzymatic Hydrogen Peroxide Detection. Issue 5 (25th January 2019) - Rezvani, E.; Hatamie, A.; Berahman, M.; Simchi, M.; Angizi, S.; Rahmati, R.; Kennedy, James; Simchi, A.
Abstract : Owing to the exceptional properties of graphene and the crucial role of substrate on the performance of electrochemical biosensors, several graphene-based hybrid structures have recently emerged, yielding improved selectivity and sensitivity. To date, most of the reported biosensors utilize solution-driven graphene flakes with drawbacks of low conductivity (due to high inter-junction contact resistant) and structural fragility. Herein, we present a conductive three-dimensional CeO2 semiconductor nanoparticles/graphene nanocomposite, as a platform for sensitive detection of hydrogen peroxide, an important molecule in fundamental biological processes. The 3D conductive graphene architecture is fabricated by chemical vapor deposition on nickel foam. The fabricated biosensor displays high sensitivity (60 μA.mM −1 ) at a low negative potential of −0.25 V, a low detection limit (<1.0 μM at S/N = 3), and a fast response (<5 s) in the range of 2.8 to 160 μM. Furthermore, density functional theory simulations show that the improved detection is not only related to the catalytic effect of ceria nanoparticles, but also to more efficient charge transfer from nanoparticles to the 3D graphene network. Moreover, it is established that the amperometric response of the biosensor is insensitive to interfering molecules such as glucose, sucrose, and potassium chloride, indicating its potential for practical applications.